A draft genome sequence of the pulse crop chickpea (Cicer arietinum L.). (2nd May 2013) - Jain, Mukesh; Misra, Gopal; Patel, Ravi K.; Priya, Pushp; Jhanwar, Shalu; Khan, Aamir W.; Shah, Niraj; Singh, Vikas K.; Garg, Rohini; Jeena, Ganga; Yadav, Manju; Kant, Chandra; et al.
Summary Cicer arietinum L. (chickpea) is the third most important food legume crop. We have generated the draft sequence of a desi‐type chickpea genome using next‐generation sequencing platforms, bacterial artificial chromosome end sequences and a genetic map. The 520‐Mb assembly covers 70% of the predicted 740‐Mb genome length, and more than 80% of the gene space. Genome analysis predicts the presence of 27 571 genes and 210 Mb as repeat elements. The gene expression analysis performed using 274 million RNA‐Seq reads identified several tissue‐specific and stress‐responsive genes. Although segmental duplicated blocks are observed, the chickpea genome does not exhibit any indication of recent whole‐genome duplication. Nucleotide diversity analysis provides an assessment of a narrow genetic base within the chickpea cultivars. We have developed a resource for genetic markers by comparing the genome sequences of one wild and three cultivated chickpea genotypes. The draft genome sequence is expected to facilitate genetic enhancement and breeding to develop improved chickpea varieties.